Management of Environmental Programs for the Arabic Language at Arrayah Sukabumi University - Septia Solihati; Nuril Mufidah; Abdul Malik Karim Amrullah (Medina-te : Jurnal Studi Islam, 2022)
The purpose of this research to describe the planning, organization, implementation and supervision of environmental programs at STIBA AR-RAAYAH. This study uses a qualitative research approach with a case study type of research. The results of this study indicate the following: First: setting daily schedules, creating daily work programmes, weekly work programmes, monthly work programmes, and annual work programmes. Second: in the organization are the Student Department, which includes BEM, the Academic Department, and the Curriculum Department. Third: Monitoring and supervising the process of environmental management of the Arabic language at STIBA AR-RAAYAH by looking at the results of the teacher's work and the results of their education, applying learning strategies/methods and the educational achievements of students, and monitoring student behavior. Fourth: The supporting factors in the formation of the Arabic language environment at Al-Raya University: good beginnings, the process of teaching and learning using the Arabic language, not owning anything that is not related to the Arabic language, native speakers, and housing. Fifth: Obstacle factors in creating the Arabic language environment at Al-Raya University: visitors, employees, non-Arabic lessons, and lecturers outside the university.